Epidemiology profile in HIV + patients with treatment of antirretrovirals drugs in the alcides carneiro university hospital, in Campina Grande city- PB - Alves, Pollianna M.; Leite, Pedro H.A.S.; Marcelino, Christiana F.; Brasileiro, Arlindo C.C.M.; Figueirêdo, Robéria L.Q.G.; Figueirêdo, Edna Q.G. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: after 23 years the aids’s discover, a lot of thing change in the knowledgements this disease. The aids is caused by retrovirus withattraction by CD4+ receipt of the lynfocits assistants, called of HIV. This inference can result in opportunistic infection, including in the oral cavity. From the oral manifestation more casual in the soropositives are fungal, bacteriological, viral infections and manifestations of unknown etiology. Objectives: the purpose of this study was determine the oral manifestations more casual that occurred the patients HIV+ of the University Hospital evaluated genus, age, race, precedence and treatment utilized. Methods: used the induced broaching, with statistical and described proceeding, whichvalues were observed behind of card index made by own searched and behind of dental trial exams realized in the patients HIV+. Results: the results showed that the genus more affected was the men (65%), 46% of the subjects showed oral lesions and the candidiasis was the more frequent. In the combinations of drugs utilizing, observed prevalence of the similar reverse transcriptase of nucleotides. Conclusion: the results showed that thedrugs utilized by patients influence in your immunity , making that discrease significantly the frequency of the oral lesions these patients.